Analytical Model and Optimization of Joint Systems in Modular Precast Foundations for Onshore Wind Turbines - Dongliang Zhang; Wantong Liu; Kun Fu; Fei Wang; Xiangguo Wu; Chu Zhao; Chao Shen; Zhiqiang Yu; Yunchao Tang (Buildings)
This study presents a comprehensive design and calculation methodology for prefabricated expansion foundations of onshore wind turbines, addressing the critical need for modular construction while ensuring structural integrity. The proposed approach encompasses both overall structural performance verification and connection joint design, considering the stiffness reduction effects of modularization. A novel punching shear capacity checking method is developed specifically for assembled expansion foundations, incorporating joint weakening factors. The research establishes equilibrium equations and verification formulas for splice joints under different loading conditions, demonstrating that the shear amplification factor at joints varies with local compressive stress. The analytical results demonstrate several key findings: (1) the derived maximum joint shear formula shows excellent agreement with finite element results across various load conditions (R2 = 0.99906); (2) the optimized shear key configuration increases the joint’s load-bearing capacity by 35% compared to conventional designs; and (3) the developed Python-based calculation system reduces the design time by 60% while maintaining accuracy within 5% of detailed FEM analysis. These quantitative outcomes validate the effectiveness of the proposed methodology and provide practical guidelines for implementing modular construction in wind energy infrastructure.